Responses of phytoplankton assemblages to iron availability and mixing water masses during the spring bloom in the Oyashio region, NW Pacific - T. Isada; A. Hattori‐Saito; H. Saito; Y. Kondo; J. Nishioka; K. Kuma; H. Hattori; R. M. L. McKay; K. Suzuki (Limnology and Oceanography, 2019)
Spring phytoplankton blooms play a major role in the carbon biogeochemical cycle of the Oyashio region, western subarctic Pacific, where the seasonal biological drawdown effect on seawater p CO 2 is one of the greatest among the world's oceans. However, the bloom often terminates before depleting macronutrients, and the initiation and magnitude of the bloom is heterogeneous. We conducted a high resolution taxonomic and physiological assessment of phytoplankton in relation to the different physicochemical water masses of Coastal Oyashio Water (COW), Oyashio water (OYW), and modified Kuroshio water (MKW) in the Oyashio region from April to June 2007. Massive diatom blooms were found in April. Then, chlorophyll a concentration, cell abundance of diatom taxa, and the maximum photosystem II photochemical efficiency ( F v / F m ) were positively correlated with the mixing ratios of COW, suggesting that the spring bloom in April was strongly affected by the intrusion of COW. In the OYW, intensive blooms occurred from the middle of May under low dissolved iron (DFe) concentration (